2000
DOI: 10.1073/pnas.090091397
|View full text |Cite
|
Sign up to set email alerts
|

A biological function for cadmium in marine diatoms

Abstract: The oceanic distribution of cadmium follows closely that of major algal nutrients such as phosphate. The reasons for this ''nutrientlike'' distribution are unclear, however, because cadmium is not generally believed to have a biological function. Herein, we provide evidence of a biological role for Cd in the marine diatom Thalassiosira weissflogii under conditions of low zinc, typical of the marine environment. Addition of Cd to Zn-limited cultures enhances the growth rate of T. weissflogii, particularly at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
377
0
11

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 639 publications
(399 citation statements)
references
References 21 publications
11
377
0
11
Order By: Relevance
“…The putative CA cDNA obtained in this fashion was sequenced and the sequence does not match a known CA from any of the (Lane & Morel, 2000). Recent work with T. weissflogii indicates that this diatom might be able to substitute Cd for Zn under Znlimiting environmental conditions (Lane & Morel, 2000). They demonstrated that the Cd-CA was different than the other CA they had previously found in T. weissflogii (Roberts et al 1997).…”
Section: Unresolved Questions: Are There More Carbonic Anhydrase Genementioning
confidence: 96%
See 1 more Smart Citation
“…The putative CA cDNA obtained in this fashion was sequenced and the sequence does not match a known CA from any of the (Lane & Morel, 2000). Recent work with T. weissflogii indicates that this diatom might be able to substitute Cd for Zn under Znlimiting environmental conditions (Lane & Morel, 2000). They demonstrated that the Cd-CA was different than the other CA they had previously found in T. weissflogii (Roberts et al 1997).…”
Section: Unresolved Questions: Are There More Carbonic Anhydrase Genementioning
confidence: 96%
“…Using this sequence information, a fragment of DNA was amplified by polymerase chain reaction (PCR) and this was used to screen a T. weissflogii cDNA library. The putative CA cDNA obtained in this fashion was sequenced and the sequence does not match a known CA from any of the (Lane & Morel, 2000). Recent work with T. weissflogii indicates that this diatom might be able to substitute Cd for Zn under Znlimiting environmental conditions (Lane & Morel, 2000).…”
Section: Unresolved Questions: Are There More Carbonic Anhydrase Genementioning
confidence: 99%
“…Lane & Morel (2000) showed that a positive effect of Cd on the growth rate of Zn-limited diatoms is mediated through an increase in cellular carbonic anhydrase (CA) activity, and that the increase is due to the expression of a Cd-specific CA. Based on previous results (Lane & Morel, 2000;Lane et al, 2005), Park et al (2007) explored the distribution and diversity of Cd-CA in 21 marine phytoplankton species under pure culture conditions and showed that 12 of them (all diatoms) expressed the Cd-specific CA. The existence of a Cd enzyme in marine phytoplankton may indicate that there is a unique selection pressure for metallo-enzymes in the marine environment by diatoms (Lane et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…CAs use a two-step "ping-pong" mechanism (2-5) that typically involves a zinc ion cofactor functioning as a Lewis acid to ionize a water molecule, although other metal ion cofactors are known (6)(7)(8). CAs are found in most eukaryotic and many microbial organisms (9,10).…”
mentioning
confidence: 99%